2013 IEEE International Conference on Systems, Man, and Cybernetics 2013
DOI: 10.1109/smc.2013.256
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Baseline Tremor under Various Microsurgical Conditions

Abstract: This paper presents the characterization and comparison of physiological tremor for pointing tasks in multiple environments, as a baseline for performance evaluation of microsurgical robotics. Previous studies have examined the characteristics of physiological tremor under laboratory settings as well as different operating conditions. However, different test methods make the comparison of results across trials and conditions difficult. Two vitroretinal microsurgeons were evaluated while performing a pointing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Surveys taken to identify directions for improvement in ophthalmic procedures have indicated that positioning accuracy and tactile perception have great importance . Surgeon accuracy has been reported to be in the range 50 to 285 µm in various tasks . This accuracy represents from 0.6 to 8.6 times the thickness of the ERM, and 14 times the ILM thickness at best.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys taken to identify directions for improvement in ophthalmic procedures have indicated that positioning accuracy and tactile perception have great importance . Surgeon accuracy has been reported to be in the range 50 to 285 µm in various tasks . This accuracy represents from 0.6 to 8.6 times the thickness of the ERM, and 14 times the ILM thickness at best.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the tip trajectory signal recorded during the rosette tasks, it was possible to estimate the tremor component by applying a band-pass ideal filter with bandwidth 6-12 Hz according to [12]. The tremor was characterized by two quantities: (i) RMS tremor , RMS (root mean square) calculated on the concatenated tremor signals from all trials: RMStremor=i=1mdi2m where d i is the 3D displacement due to tremor (Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The requirements for vision, depth perception, and fine motor control are high (Table 0.2), exceeding the fundamental physiological capability of many individuals [36,75,148]. A primary cause of tool positioning error is physiological tremor [201]. Even when microsurgical procedures [73] are successfully performed, in the presence of tremor they require greater concentration and effort and are attended by greater risk.…”
Section: Human Factors and Technical Challengesmentioning
confidence: 99%